Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Optik Minang Bukitinggi - Novalinda , Rina (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
This research design uses descriptive quantitative methods. The population in this study were consumers at Optik Minang Bukittinggi from 16 July to 19 July 2024. Data was collected through a research questionnaire using a checklist. The research results showed that respondents did not fully understand the importance of service quality on customer satisfaction. A total of 44 respondents (86.3%) were satisfied with the quality of service at Optik Minang and 7 respondents (13.7%) were dissatisfied with the quality of service at Optik Minang. Based on the results of this research, there are several suggestions submitted to (1) Optical Owners are expected to continue to maintain and improve the quality of service (2) ROs are expected to work professionally (3) Optical Refraction Academy is expected to be used as scientific information material in the field of Optical Refraction. (4) For future researchers, the author hopes that further research can be carried out with other independent variables so that more variables that influence consumer satisfaction at Optik can be identified.